FUNGSI PENGAWASAN TERHADAP PENCANTUMAN KLAUSUL EKSONERASI PADA PRODUK BARANG DAN JASA BERDASARKAN UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN DI KOTA PEKANBARU - Rezky Yarman; Mardalena Hanifah; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
The use of standard clauses as a result of the principle of freedom ofcontract which states that every person is free to form, kind, type and content ofthe agreement does not violate laws and regulations, public order and decency.Developments today many businesses that include clauses that contain limitingconditions, or even remove completely the responsibility that should be charged tothe manufacturer. This creates an imbalance of bargaining power betweenproducers and consumers.Guidance and oversight functions carried out by the government and societyin the inclusion of the exoneration clause in Pekanbaru based on Law No. 8 of1999 on Consumer Protection is not running as mandated by the law. This is dueto the factors that influence it. In terms of the Government represented by BPSKand LPKSM, In conducting the guidance and supervision of the inclusion of theexoneration clause in Pekanbaru influenced by factors inhibiting namelyInstitutional Factors, Finance, and Human Resources. In terms of communitysupervision inclusion of factors that affect the exoneration clause is a factor oflegal awareness, education, and socialization.Efforts that can be done to minimize the inclusion of the exoneration clausein Pekanbaru. In terms of government attempts to do is to providerecommendations and advice their inclusion exoneration clause by businesses andprovide information to the Industry and Trade of the limiting factors that affectthe development and supervision.Key Word : Exoneratioin Clause-Consumer Protection